2021
DOI: 10.25259/cjhs_50_2020
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic imaging study of luminal diameter of the circle of Willis in patients with ischemic stroke

Abstract: Objectives: Stroke or cerebrovascular accident is associated with defects in the circle of Willis; the vascular network that supplies the brain. There is currently lack of literature on the involvement of the circle of Willis in patients with stroke or its association with impending stroke. The objective of the study was to evaluate luminal diameter of arteries that constitute the circle of Willis in patients with stroke using computed tomography angiography (CTA) and magnetic resonance imaging (MRI) scans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Studies have demonstrated a classical and complete pattern of a circle of Willis where all the vessels are intact and crucial for a continuous supply of blood. 6,8,[10][11][12][13][14][15] or the duration and extent of obstruction needs to be answered. To address these deficiencies, it is important to investigate how morphological patterns of the circle of Willis influence stroke development using CTA and MRI as diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Studies have demonstrated a classical and complete pattern of a circle of Willis where all the vessels are intact and crucial for a continuous supply of blood. 6,8,[10][11][12][13][14][15] or the duration and extent of obstruction needs to be answered. To address these deficiencies, it is important to investigate how morphological patterns of the circle of Willis influence stroke development using CTA and MRI as diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…These innovative quantitative assessments of acute ischemic stroke with nonenhanced computed tomography are poorly utilized in most Nigerian hospitals. Subsequently, 90.9 -100% of ischemic stroke patients do not receive the appropriate treatment with resultant high rate of mortality and disability where majority of the patients become vulnerable to having secondary complications of the disease (stroke) including lobar atrophy, white matter lesions, cerebral infarct, in addition to structural changes/morphological patterns in the circle of Willis: the major arterial supply to the brain (Igiri et al, 2017;Paulinus et al, 2017;Udo-Affah et al, 2020;Paulinus et al, 2021;Paulinus et al, 2023). The study therefore, focused on patients who presented late (4.5 to 24 hours) for nonenhanced CT, were eligible for treatment with intravenous thrombolysis or endovascular thrombectomy based on ASPECTS, pc-ASPECTS and Hounsfield unit (HU) ratio.…”
Section: Introductionmentioning
confidence: 99%